PERLINDUNGAN HUKUM ATAS HAK CIPTA JIPLAKAN KONTEN PLATFORM TIKTOK - Jamil, Nury Khoiril Jamil; Rato, Dominikus; Setyawan, Fendi (Institut Agama Islam Negeri Fattahul Muluk Papua, 2023)
Abstract This research analyzes legal protection for creators in creating content. The fast flow of content on TikTok has a lot of potential for plagiarism, which legally, copyright has its own protection for creators, both morally and even commercially. It is important to ensure legal protection, both preventive and even repressive, for creators that provides justice for creators in their work. In this research, there are two problem formulations, namely 1) How is Copyright Protection for Tiktok Creator Content for Their Creations? 2) What are the legal remedies for copyright infringement against plagiarized on TikTok content? This research uses a type of normative research method, namely research with the object of study being legal and regulatory documents and library materials with a statutory approach and a conceptual approach. This research resulted in, 1) TikTok's terms of service contain a license agreement which may violate the provisions of Article 82 of the HC Law, which limits the making of license agreements, thereby guaranteeing legal protection for the copyright of TikTok creators. This still raises legal issues; 2) The legal remedy that can be taken for losses in content created by creators is to sue civilly, because in the context of TikTok content, they only have moral rights and there are no economic rights in it.